Fractal properties of correlated invasion percolation patterns - López, Raúl Horacio (2003)
We present results on Monte Carlo simulations for invasion percolation with trapping considering the presence of spatial size correlations, a problem which is relevant to multiphase flow in field scale of porous media. The correlations are generated through the dual site bond model, characterized by a spatial correlation length r0, which depends on the overlap between site and bond distributions. Our results indicate that in two-dimensional lattices the fractal dimension of the sample-spanning cluster, is non-universal and vary with the correlation. Comparison with other authors recent findings is presented.